Performance Evaluation of Maximum Power Point Tracking Approaches and Photovoltaic Systems - Islam, Haidar; Mekhilef, Saad; Shah, Noraisyah Mohamed; Tey, Kok Soon; Seyedmahmousian, Mehdi; Horan, Ben; Stojcevski, Alex (MDPI, 2018)
This paper elaborates a comprehensive overview of a photovoltaic (PV) system model, and compares the attributes of various conventional and improved incremental conductance algorithms, perturbation and observation techniques, and other maximum power point tracking (MPPT) algorithms in normal and partial shading conditions. Performance evaluation techniques are discussed on the basis of the dynamic parameters of the PV system. Following a discussion of the MPPT algorithms in each category, a table is drawn to summarize their key specifications. In the performance evaluation section, the appropriate PV module technologies, atmospheric effects on PV panels, design complexity, and number of sensors and internal parameters of the PV system are outlined. In the last phase, a comparative table presents performance-evaluating parameters of MPPT design criterion. This paper is organized in such a way that future researchers and engineers can select an appropriate MPPT scheme without complication.